KISAH TAMAN EDEN SEBAGAI GAMBARAN IDEAL RELASI EKOLOGIS ANTAR CIPTAAN - Yan Okhtavianus Kalampung; Adriana Awumbas; Halomoan Alfian Londok (DA'AT : Jurnal Teologi Kristen, 2020)
This essay argues that the story of the Garden of Eden is a genuine image of the creational relation between humans and nature. Using the perspective of ecological analysis, this essay shows that the story of the Garden of Eden consequently presented the anthroposentical, biosentrical, and ecosentrical, relation between the creation of God. It appeared that the Garden of Eden is the representation of the idea of good relationship between human and nature before the human greedness destroy the perfect relation. This story also comes with a reminder to human nature responsibility with his/her environment in the first place